Madrasah's Head's Strategy In Increasing Teacher Performance Motivation In MTs Tahfidz Manbaul Kirom - Mustaqim, Hijrah Rijal; Arafat, Yasir; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine what strategies are used and the efforts to overcome the obstacles of the Principal of Madrasah Tsanawiyah Tahfidz Manbaul Kirom in increasing teacher performance motivation. This study uses a qualitative method. Data collection techniques are interviews, observation and documentation. Data were analyzed using interview analysis techniques, observation and documentation. The results showed that the strategies used by madrasah principals in general were able to generate motivation for teacher performance, although there were still teachers who had not significantly increased their motivation. The strategy used by the head of madrsah in general has been able to generate motivation for teacher performance, still using general methods or methods, the principal of Madrasah Tsanawiyah Tahfidz Manbaul Kirom must have a special strategy or approach so that teachers are motivated to improve their performance.